(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
This article explores the innovation potential of the staff at industrial enterprises. One of the main goals of the research was determining the factors influencing the development of the innovative potential of the company’s employees. The authors analyzed the company’s internal regulatory documents that regulate the enterprise’s innovation policy. The relevance of the research is confirmed by the increasing interest of companies in innovation. This manifests itself both in the changing organizational structure of enterprises and a new approach to human resource management, for instance, the revision of the key performance indicators of employees. Some authors mention that the changes and social transformations determine the need for organizations to search for alternatives that can improve performance, facilitate the achievement of goals and improve the provision of services. This confirms the relevance of the research topic and the need to study the factors influencing the development of the innovative potential of the employees. Having analyzed the internal documents regulating the innovation policy of the enterprise, we determined the organizational structure of the innovation management and the stakeholders. Thus, we could propose targeted recommendations and determine how to improve the system to develop the innovation potential of the staff.